Neurotransmitter and Intestinal Interactions: Focus on the Microbiota-Gut-Brain Axis in Irritable Bowel Syndrome - Chen, Minjia; Ruan, Guangcong; Chen, Lu; Ying, Senhong; Li, Guanhu; Xu, Fenghua; Xiao, Zhifeng; Tian, Yuting; Lv, Linling; Ping, Yi; Cheng, Yi; Wei, Yanling (Frontiers in Endocrinology, 2022)
Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder of unknown etiology. IBS is caused by a disruption in the gut-brain axis. Given the importance of the gut microbiota in maintaining local and systemic homeostasis of immunity, endocrine, and other physiological processes, the microbiota-gut-brain axis has been proposed as a key regulator in IBS. Neurotransmitters have been shown to affect blood flow regulation, intestinal motility, nutrient absorption, the gastrointestinal immune system, and the microbiota in recent studies. It has the potential role to play a function in the pathophysiology of the gastrointestinal and neurological systems. Transmitters and their receptors, including 5-hydroxytryptamine, dopamine, γ-aminobutyric acid, and histamine, play an important role in IBS, especially in visceral sensitivity and gastrointestinal motility. Studies in this field have shed light on revealing the mechanism by which neurotransmitters act in the pathogenesis of IBS and discovering new therapeutic strategies based on traditional pharmacological approaches that target the nervous system or novel therapies that target the microbiota.